Association of sleep duration with overweight and obesity among school-aged children and adolescents in Pakistan—An empirical cross-sectional study - Moazzam Tanveer; Alexios Batrakoulis; Ejaz Asghar; Andreas Hohmann; Serge Brand; Matheus S. de Sousa Fernandes; Luca P. Ardigò; Georgian Badicu (Journal of Education and Health Promotion)
Background: Overweight and obesity pose significant public health challenges for children and adolescents worldwide, with escalating prevalence rates in Pakistan, leading to long-term health consequences. Proximal environments, including parental, peer, school, and community influences, are pivotal in shaping children’s health behaviors during developmental stages. This study investigates the association between sleeping behaviors and overweight/obesity among Pakistani school-aged children and adolescents (9–17 years). Materials and Methods: A population-based cross-sectional study enrolled 4108 participants from 62 schools across randomly selected districts in central Punjab province. Overweight and obesity were determined using WHO references. Statistical analyses included Chi-square tests, Pearson correlation coefficients, and logistic regressions. Results: The study analyzed the prevalence and associations of sleep duration with body weight status among Pakistani school-aged children and adolescents. Significant differences were observed in sleep patterns across different school levels and sexes. Boys were more likely to be short or long sleepers compared to girls, with weekday short sleep significantly associated with lower rates of overweight (9.0% vs 14.6%, P < 0.001) and obesity (3.8% vs 2.6%, P < 0.001). On weekends, short sleep was linked to higher prevalence of overweight (9.6%, P = 0.019) and obesity (6.2%, P < 0.001) compared to normal sleepers. Linear regression revealed that weekday sleep duration (β = 0.213, P < 0.001), weekend sleep duration (β = 0.142, P < 0.001), and sleeping problems (β = 0.182, P < 0.001) were positively associated with higher body weight status, explaining 11.0% of the variance in weight status. Logistic regression indicated that short sleepers had significantly higher odds of being overweight (OR = 2.69, P < 0.001) and obese (OR = 5.65, P < 0.001) compared to normal sleepers. Long sleep also showed significant associations with overweight (OR = 2.41, P < 0.001) and obesity (OR = 1.73, P < 0.001). Conclusions: Sleeping behaviors emerge as significant contributors to body weight-status issues among Pakistani school-aged children and adolescents. Understanding these factors is imperative for effective policy and program development to combat childhood obesity. Targeted intervention strategies tailored to vulnerable groups are essential for public health efforts. Insights from this study provide valuable guidance for addressing this urgent health concern.